War and the militarization of British Army medicine, 1793-1830 - Kelly, Catherine 1974- (Studies for the Society for the Social History of Medicine, 2011)
This study demonstrates the emergence and development of the identity of the 'military medical officer' and places their work within the broader context of changes to British medicine during the first half of the nineteenth century